Audit Sistem Informasi Sumber Daya Manusia Pada Training Center Di Bali Menggunakan Framework COBIT 4.1 - Sinondang Tapianauli, Dea Bella Rossa (Jurnal Nasional Ilmu Komputer, 2025)
Smart learning is a type of IT training center for private or government companies that prioritizes improving employee skills for various different needs with materials that are in accordance with customer needs, at the right time and place. It is clear that increasing the amount of training must be balanced with improving the quality of existing human resources. To see all that, system control and audit must be carried out. This will allow you to see how effective the system is and maximize the benefits obtained by the company by reducing risks and expenses. By using COBIT 4.1, control techniques can be applied and adjusted to IT goals and company goals. It is necessary to measure the level of alignment between IT goals and company goals.